The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1111/j.1476-5381.1973.tb08200.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of noradrenaline from the cat spleen by sodium deprivation

Abstract: Summary1. The endogenous noradrenaline content of cat spleen slices was markedly reduced when the slices were incubated at 370 C in a medium in which sodium was replaced by sucrose, lithium, choline or potassium. Depletion of tissue noradrenaline was accounted for by its release into the incubating medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 29 publications
(36 reference statements)
4
22
0
Order By: Relevance
“…The result is consistent with data presented by Garcia and Kirpekar (6) in the cat spleen. On the other hand, it has been reported that in the rat heart, increases in the release and decreases in the stores of 3H-noradrenaline induced by sodium deprivation especially when replaced with choline,…”
supporting
confidence: 83%
“…The result is consistent with data presented by Garcia and Kirpekar (6) in the cat spleen. On the other hand, it has been reported that in the rat heart, increases in the release and decreases in the stores of 3H-noradrenaline induced by sodium deprivation especially when replaced with choline,…”
supporting
confidence: 83%
“…Tissues lose their noradrenaline content when exposed to a lowsodium environment (Kirpekar & Wakade, 1968a;Bogdanski & Brodie, 1969;Garcia & Kirpekar, 1973). Experiments carried out to see if bretylium was released from the sympathetic nerve terminals by exposure to sodium-free medium clearly demonstrated that like noradrenaline, bretylium was released leading to an impairment of the ability of the tissue to retain [3H] -noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…Ten min after the last washout the control preparation was exposed to bretylium (20;ig/ml for 5 minutes). (Kirpekar & Wakade, 1968a;Bogdanski & Brodie, 1969;Garcia & Kirpekar, 1973 (Figure 5, column B). On the other hand, in the half atrium treated with bretylium in normal Krebs, and then switched to sodium-free (sucrose) Krebs, retention of [ 3 H] -noradrenaline was also markedly decreased ( Figure 5, column C).…”
Section: Effect Of Potassium Deprivation On the Abili7 Of Bretylium mentioning
confidence: 99%
“…The major mechanism involved in this increase in the output of noradrenaline seems to be an inhibition of the retention rather than that of the reuptake, because guanethidine, a potent inhibitor of the uptake (Hertting, Axelrod & Patrick, 1962), did not potentiate the efflux induced by low sodium. Garcia & Kirpekar (1973) demonstrated that the various procedures which are known to inhibit Na+, K+-activated ATPase or the sodium potassium pump, induce the efflux of noradrenaline. However, the present result, showing that guanethidine inhibits the output of noradrenaline induced by low sodium, is not explicable in terms of the activation of this enzyme in the adrenergic nerve endings because the drug does not modify the myocardial transport ATPase activity (Misu & Nishio, 1978).…”
Section: Resultsmentioning
confidence: 99%